Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar Bahasa Indonesia di SMP Muhammdiyah 5 Surakarta - Metha Dewa Yani Putri (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2022)
This study aims to determine the benefits of the school library as a learning resource for learning Indonesian at SMP Muhammadiyah 5 Surakarta. This research is a descriptive qualitative research by using the principal, Indonesian teacher, and students as research subjects. The results of the study indicate that the pattern of utilization of the school library used is to ensure that students complete learning tasks by using the school library as a learning resource. The purpose of the utilization pattern is to instill the attitudes and awareness of students to read. The supporting factors are the availability of the school library, the enthusiasm of the teachers, the enthusiasm of the students, the arrangement of good books, the existence of a conditional lesson plan. The inhibiting factors are the absence of librarian, the absence of a clear library structure, a lot of time consuming lessons, and the lack of supporting learning resources.